Prediction of cross second virial coefficients for dimer H2-O2 from ab initio calculations of intermolecular potentials - Tất và cộng sự, Phạm Văn (Vietnam Journal of Chemistry, 2014)
The intermolecular interaction potentials of the dimer H2-O2 were calculated from quantum mechanics, using coupled-cluster theory CCSD(T) and correlation-consistent basis sets aug-cc-pVmZ (m = 2, 3); the results were extrapolated to the basis set limit aug-cc-pV23Z. The quantum mechanical results were used to construct 5-site pair potential functions. The cross second virial coefficients of the dimer hydrogen-oxygen were obtained by integration; in these cases corrections for quantum effects were included. The results agree well with experimental data and empirical correlations.